Viral load strategy: impact on risk behaviour and serocommunication of men who have sex with men in specialized care. (9th July 2016) - Kuhn, E.; Potthoff, A.; Dirks, H.; Borgmann, R.; Esser, S.; Scherbaum, N.; Brockmeyer, N.H.; Skaletz‐Rorowski, A.
Abstract: Background: Incidence and prevalence of HIV are continuously high in German men, who have sex with men (MSM). Different transmission risk minimizing strategies have been observed. The viral load strategy rates patients unlikely to be sexually infectious if their viral load under effective therapy is stably suppressed during 6 months and no other sexually transmitted infections are present. Objectives: We aim to objectify the current popularity of the viral load strategy, the adherence to basic conditions and its impact on risk behaviour and serocommunication. Until now, no data on a German sample of HIV‐positive MSM in regular specialized outpatient care are available. Methods: Cross‐sectional study with group comparisons between user group and non‐user‐group of the viral load strategy. Self‐report questionnaires were conducted with 269 sexually active German HIV+MSM under effective treatment in specialized outpatient care. Structured interviews gathered additional information about approach to and realization of definite action levels concerning sexual risk behaviour and transmission risk minimizing strategies. Results: Twenty‐seven of 269 participants (10%) affirmed knowledge of having an undetectable viral load and stated this to be criteria for unprotected sexual behaviour. This subgroup reported more unprotected insertive ( P = 0.018) and receptive anal intercourse ( P = 0.042), more anonymous sex partners ( P = 0.008) and less consistent safer sex. Analysing serocommunication, less addressing HIV/AIDS in general ( P = 0.043) and less disclosing to sex partners ( P = 0.023) was found, especially in anonymous settings. Differentiating serocommunication characteristics, a focus on seroguessing was depicted. Conclusions: The user group of the viral load strategy is small. But a less frequent, more reactive and assumptive serocommunication leads to an imprecise information exchange paired with higher frequency of risky behaviour, especially in anonymous settings, where frank serocommunication is often avoided. The targeted group of the viral load strategy diverges greatly from the user group.